PELUANG DAN TANTANGAN: PERANAN FINANCIAL TECHNOLOGY SYARIAH DALAM MEMAJUKAN UMKM DI KOTA MEDAN - Edi, Sarwo; Husna, Asmaul (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2023)
Utilization of technology can provide many convenience facilities in every business activity with fast access. One of the technological developments that has become the dynamics of business development today is Financial Technology. This paper aims to describe the role of Fintech in the progress of MSMEs in Medan City along with an explanation of the opportunities and challenges faced. This research was conducted through qualitative descriptive studies and analysis, where data were obtained from various reference sources regarding the topics and issues discussed. Data collection techniques used a literature study approach through various research journals, national and international articles. This research explains how the opportunities and challenges of Fintech for the development of MSMEs will be faced in the future. The results of the study show that Fintech has considerable potential for the development of MSMEs in Indonesia. Fintech can help MSMEs in providing convenience and efficiency in terms of technology-based financial management including digitizing financial reports, payment technology and online-based loans.